Prioritarianism in practice - Adler, Matthew D.; Norheim, Ole Frithjof (2022)
Prioritarianism is an ethical theory that gives extra weight to the well-being of the worse off. In contrast, dominant policy-evaluation methodologies, such as benefit-cost analysis, cost-effectiveness analysis, and utilitarianism, ignore or downplay issues of fair distribution. Based on a research group founded by the editors, this important book is the first to show how prioritarianism can be used to assess governmental policies and evaluate societal conditions. This book uses prioritarianism as a methodology to evaluate governmental policy across a variety of policy domains: taxation, health policy, risk regulation, education, climate policy, and the COVID-19 pandemic. It is also the first to demonstrate how prioritarianism improves on GDP as an indicator of a society's progress over time. Edited by two senior figures in the field with contributions from some of the world's leading economists, this volume bridges the gap from the theory of prioritarianism to its practical application.
Title from publisher's bibliographic system (viewed on 27 Jun 2022).
Keywords: Social indicators; Economic indicators; Quality of life